Emerging antiviral resistant strains of influenza A and the potential therapeutic targets within the viral ribonucleoprotein (vRNP) complex - Davis, Alicia M (BioMed Central, 2014)
Emerging antiviral resistant strains of influenza A virus are greatly limiting the therapies available to stop aggressive infections. Genome changes that confer resistance to the two classes of approved antivirals have been identified in circulating influenza A viruses. It is only a matter of time before the currently approved influenza A antivirals are rendered ineffective, emphasizing the need for additional influenza antiviral therapies. This review highlights the current state of antiviral resistance in circulating and highly pathogenic influenza A viruses and explores potential antiviral targets within the proteins of the influenza A virus ribonucleoprotein (vRNP) complex, drawing attention to the viral protein activities and interactions that play an indispensable role in the influenza life cycle. Investigation of small molecule inhibition, accelerated by the use of crystal structures of vRNP proteins, has provided important information about viral protein domains and interactions, and has revealed many promising antiviral drug candidates discussed in this review.